Additive Manufacturing of Oral Tablets: Technologies, Materials and Printed Tablets - Alperen Abaci; Christina Gedeon; Anna Kuna; Murat Guvendiren (MDPI AG, 2021)
Additive manufacturing (AM), also known as three-dimensional (3D) printing, enables fabrication of custom-designed and personalized 3D constructs with high complexity in shape and composition. AM has a strong potential to fabricate oral tablets with enhanced customization and complexity as compared to tablets manufactured using conventional approaches. Despite these advantages, AM has not yet become the mainstream manufacturing approach for fabrication of oral solid dosage forms mainly due to limitations of AM technologies and lack of diverse printable drug formulations. In this review, AM of oral tablets are summarized with respect to AM technology. A detailed review of AM methods and materials used for the AM of oral tablets is presented. This article also reviews the challenges in AM of pharmaceutical formulations and potential strategies to overcome these challenges.